A Theme–Rheme Analysis of International News Reports on Russia’s LGBT Policy - M. Asril Marpaung (Journal Of Global Research Publications, 2026)
This study examines how thematic organization contributes to the construction of state power and social positioning in international news discourse. Drawing on Halliday’s Systemic Functional Linguistics, with a specific focus on Theme–Rheme structure, the study analyses a BBC news report published in November 2023 on the Russian Supreme Court’s decision to designate the so-called “international LGBT movement” as an extremist organization. Using a qualitative textual approach, the text is segmented into clauses and analyzed to identify patterns of thematic choice and progression. The findings reveal a consistent foregrounding of institutional actors, such as state authorities and legal bodies, in Theme position when reporting legal actions and policy decisions, while members of the LGBT community and civil society figures are predominantly thematized in clauses expressing reactions, personal experiences, and anticipated consequences. This asymmetric thematic distribution constructs a discourse in which state authority is positioned as the primary agent of action, whereas affected social groups are framed as respondents to institutional power. The study demonstrates that ideological meanings in news discourse may be realized implicitly through grammatical organization rather than explicit evaluative language, and it highlights the value of Theme–Rheme analysis for examining power relations in contemporary international news reporting.